In Situ Observation of Thiol Michael Addition to a Reversible Covalent Drug in a Crystalline Sponge. (11th March 2016) - Duplan, Vincent; Hoshino, Manabu; Li, Wei; Honda, Tadashi; Fujita, Makoto
Abstract: A reversible Michael addition reaction between thiol nucleophiles and cyanoenones has been previously postulated to be the mechanism‐of‐action of a new family of reversible covalent drugs. However, the hypothetical Michael adducts in this mechanism have only been detected by spectroscopic methods in solution. Herein, the crystallographic observation of reversible Michael addition with a potent cyanoenone drug candidate by means of the crystalline‐sponge method is reported. After inclusion of the cyanoenone substrate, the sponge crystal was treated with a thiol solution. Subsequent crystallographic analysis confirmed the single‐crystal‐to‐single‐crystal transformation of the substrate into the impermanent Michael adduct.